Transcriptomic analysis reveals prolonged neurodegeneration in the hippocampus of adult C57BL/6N mouse deafened by noise - Lee, Sang-Youp; Lee, Ho Sun; Park, Min-Hyun (Frontiers in Neuroscience, 2024)
Introduction Several studies have reported a significant correlation between noise-induced hearing loss and cognitive decline. However, comprehensive analyses of this relationship are rare. This study aimed to assess the influence of hearing impairment on cognitive functions by analyzing organ samples in the afferent auditory pathway of deafened mice using mRNA sequencing. Methods We prepared 10 female 12-week-old C57BL/6N mice as the experimental and control groups in equal numbers. Mice in the experimental group were deafened with 120 dB sound pressure level (SPL) wideband noise for 2 h. Cochlea, auditory cortex, and hippocampus were obtained from all mice. After constructing cDNA libraries for the extracted RNA from the samples, we performed next-generation sequencing. Subsequently, we analyzed the results using gene ontologies (GOs) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway databases for differentially expressed genes (DEGs) of each organ. Results Our results revealed 102, 89, and 176 DEGs for cochlea, auditory cortex, and hippocampus, respectively. We identified 294, 203, and 211 GOs; 10, 7, and 17 KEGG pathways in the cochlea, auditory cortex, and hippocampus, respectively. In the long term (12 weeks) from noise-induced hearing loss, GOs and KEGG pathways related to apoptosis or inflammation persisted more actively in the order of hippocampus, auditory cortex, and cochlea. Discussion This implies that the neurodegenerative effects of noise exposure persist more longer time in the central regions.